Nitrogen storage and remobilization in ash (Fraxinus excelsior) under field and laboratory conditions - Marmann, Peter; Wendler, Renate; Millard, Peter; Heilmeier, H. (Trees (Berlin, West), 1997)
Storage and remobilization of nitrogen (N) were studied in ash trees (Fraxinus excelsior) under both field and greenhouse conditions. Experiments in the greenhouse providing 15N labelled fertilizer to the trees showed that the major quantity of N remobilized during subsequent spring was from the roots, and only a small amount from the stem. This corresponded with a loss of soluble N (proteins and low-molecular-weight compounds) from both roots and stem. On the two field sites, which differed in water availability, there was a decrease in bark N content during leaf growth, but on the dry site net N export from the bark was sustained throughout the whole vegetation period. Remobilized N was derived from soluble proteins and low-molecular-weight compounds on the moist site, which was demonstrated by the seasonal dynamics of a 56 kDa polypeptide in bark and wood. On the dry site, lower contents of soluble proteins were associated with smaller amounts of N remobilized compared to the moist site. Uptake studies of 15N labelled fertilizer indicated a higher contribution of current uptake to leaf N increment during spring at the dry site compared to the moist site. Differential N availability during the season had a decisive effect on the nitrogen storage dynamics at the two sites. Thus the influence of current N supply on N remobilization and storage as found in the greenhouse-grown plants could be verified under field conditions.